Entrepreneurship Training through Softskill and Computerization Strengthening Elaboration for Youth Organization in Gresik - Sukaris Sukaris (OJS Universitas Muhammadiyah Gresik, 2018)
Changes that occur at this time, especially in real business both as individuals and organisations, none of them has not changed. These changes certainly must be positively addressed as an affirmation of following and increasing capabilities so as not to be crushed by these changes. Training with the elaboration of strengthening soft skills and computerisation is carried out as one of the answers to these changes, especially in improving the ability of technology-based entrepreneurship. Specific goals and targets to be achieved Entrepreneurial training through the elaboration of strengthening soft skills and computerisation are; a). Equipping participants especially youth members to have the right understanding in achieving success; b) Providing ability to make long-term planning; c) Provide motivations for success; and d) Providing ability with the use of technology in entrepreneurship. The method used for this achievement is a semi workshop wherein the initial stage of the activity is the provision of material related to the achievement of the first, second and third goals while for the computer workshop as the achievement of the fourth goal. The activity is carried out for two days with a duration of 16 hours face to face or every day. The implementation of these activities was carried out by the Karangtaruna team while from the Muhammadiyah University Gresik team as facilitators. This activity is also expected to provide material that is following the needs of youth members as partners in the present and future in entrepreneurship.